Prognostic accuracy of blood cell count ratios in predicting adverse outcomes in crush syndrome patients - Taner Karlidag; Olgun Bingol; Baran Sarikaya; Omer Halit Keskin; Atahan Durgal; Guzelali Ozdemir (Scientific Reports)
Abstract The rationale behind this study was the lack of an accurate predictor to facilitate treatment management and anticipate prognosis in crush syndrome. Our research aimed to investigate the following: (1) Is there a correlation between the ratios of blood cell counts upon admission and the adverse outcomes of crush syndrome? and (2) if such a correlation exists, what are the precise thresholds of blood cell count ratios for predicting these adverse outcomes? In this single-centered and retrospective design study, we analyzed all patients admitted to our hospital after Kahramanmaras Earthquake. The data on length of stay in the ICU and mortality status were obtained using our hospital system. Ratios of blood cell count were calculated and recorded at the time of admission. The NLR values in admission were significantly higher in patients with amputation, patients who received intensive care unit (ICU), and patients who died. (p < 0.001, p < 0.001 and p = 0.001, respectively). The MLR values were significantly increased in patients who underwent amputation and patients who received ICU (p < 0.001 and p = 0.003, respectively). NAR values in admission were significantly higher in patients with amputation, patients who received intensive care unit (ICU), and patients who died (p < 0.001, p < 0.001, and p = 0.002, respectively). In addition, according to binary logistic regression analysis, with a CLR value of > 109.844, the risk of amputation increases 8.188 fold; with a CLR value of > 64.518, the possibility of ICU admission requirement increases 10.117 fold, and with a CLR value of > 116.00, the risk of death increases 5.519 fold. Ratios of blood cell count such as NLR, MLR, NAR, and CLR offer a reasonable prognostic accuracy in predicting adverse outcomes and mortality in patients with crush syndrome. Therefore, for better disaster management in the future, the determination of these values at admission should be used as an adjunct tool for predicting prognosis in patients with crush syndrome.